2019
DOI: 10.1108/jefas-09-2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of innovation

Abstract: Purpose This paper aims to study the influence of innovation on micro, small and medium-sized enterprises (MSME) performance in Colombia through the 403 MSMES survey analysis. In particular, this paper measures the effect of participation in R&D alliances, product innovation and process innovation on it. Design/methodology/approach MSME performance is measured through a composite index, estimated through principal components analysis using polychoric correlations, which is based on eight self-reported as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…Networks can provide opportunities or create restrictions in the organisation's performance (Kilduff and Brass, 2010; Restrepo-Morales et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Networks can provide opportunities or create restrictions in the organisation's performance (Kilduff and Brass, 2010; Restrepo-Morales et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2018) argue that organizational structures, work climate, knowledge development, and human resource well-being are some factors that determine the innovation capacity of medium-sized firms. Additionally, Restrepo-Morales et al (2019) identified R&D activities and alliances as the determinants of the innovativeness of SMEs in Colombia. At the same time, Babuchowska and Marks-Bielska (2021) reveal that streamlining work, improvement in quality, and compliance with the requirements as some of the determinants of innovation in dairy farms in Poland.…”
Section: Determinants Of Innovationmentioning
confidence: 99%
“…The growth of Indian MSMEs can be guided by the theory of production (TOP) and resource-based view (RBV). The theory of production states that the business firms decides how much of each commodity it sells (its 'outputs' or 'products'), it produces, and how much of each kind of labour, raw material, fixed capital good, and so on, it employs (its 'inputs' or 'factors of production') (Restrepo-Morales et al, 2019). The firm's focus is to determine the cheapest possible factors of production such as land, raw material, capital and labour which will produce the desired level of output.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%